Adjuvant denosumab for early breast cancer–Evidence and controversy - Laura Moretti; Laura Richelmi; Deborah Cosentini; Rebecca Pedersini; Salvatore Grisanti; Vito Amoroso; Alfredo Berruti; Marta Laganà (Breast)
The efficacy of adjuvant denosumab in combination with hormonotherapy in breast cancer patients was investigated in two randomized trials, ABCSG-18 and D-Care, but the results were mixed with respect to the impact of this drug on disease-free survival. However, the ABCSG-18 study has achieved its primary goal: prevention of clinical fractures. Therefore, the protective role of Denosumab on bone fragility induced by estrogen deprivation, already demonstrated in post-menopausal women, has been validated in the breast cancer setting.